Effectiveness of verbal and non-verbal organizational communication in achieving security and occupational safety for workers in industrial establishment: Field study at Sonatrach Foundation (Ain Saleh Gas Project) - Allouti, Achour (Journal of Human Sciences, 2022)
The aim of this study is to identify the effect-iveness of communication tools and their relationship to industrial security, and to detect the obstacles they face, where a simple random sample of 145 members of the study population was taken, and the researcher adopted in the analysis of data and information program (SPSS). We also used the descriptive approach. The study reached the following results: - Detect the existence of a different electronic communication and non-verbal and written average flow of information from the admin-istration to the implementers and supervisors, either through reports or through announcements, and the use of multiple languages. - Using oral communication more often, where workers rely on direct contact with the supervisor or the use of meetings to communicate all their concerns, despite their preference to contact and meet directly with the manager.